(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Effective asset provisioning is a difficult task in the ever-changing cloud computing environment, as both insufficient and excessive allocation can negatively impact system performance. Due to this dilemma, scholars are investigating novel approaches, with a growing emphasis on proactive provisioning strategies that foresee and address resource requirements ahead of time.